Effect of a Stable Magnetic Field on Silicon Properties - M.I. Timoshina; E.V. Akimov; A.A. Gulamov; A.V. Kochura; M.B. Dobromyslov (Журнал нано- та електронної фізики)
The effect of a constant magnetic field (0.17 T) on microhardness, kinetics of photoconductivity decline and electro conductivity in silicon crystals is studied. The nature of changes of micromechanical and electrophysical characteristics in samples is investigated as a function of time elapsed after magnetic treatment. The results obtained are discussed in terms of magnetic field stimulated processes occurring in a subsystem of structural defects.